sum sum I_1 sum sum sum I_3 sum const I_1 sub sub I_1 sub sub sub I_3

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
//sum(x, 0) = ...(x)
sum(x, 0) = I_1(x)
//sum(x, y+1) = ...(x, y, sum(x, y))
sum(x, y+1) = s I_3(x, y, sum(x, y))
//p(0) = const
p(0) = 0
//p(x+1) = ...(x, p(x))
p(x+1) = I_1(x, p(x))
//sub(x,0) = ...(x)
sub(x,0) = I_1(x)
//sub(x,y+1) = ...(x, y, sub(x, y))
sub(x,y+1) = p I_3(x, y, sub(x, y))
//sgn(0) = const
sgn(0) = 0
//sgn(x+1) = ...(x, sgn(x))
sgn(x+1) = s o I_1(x, sgn(x))
//mul(x, 0) = ...(x)
mul(x, 0) = o(x)
//mul(x, y+1) = ...(x, y, mul(x, y)) = ...[...(x, y, mul(x, y)), ...(x, y, mul(x, y))]
mul(x, y+1) = sum[I_1(x, y, mul(x, y)), I_3(x, y, mul(x, y))]
//r(0) = const
r(0) = 0
r(x+1) = s(r(x)) * sgn(5-s(r(x))) //для неё
//r(x+1) = ...(x, r(x)) = ...[...(x, r(x)), ...(x, r(x))]
r(x+1) = mul(s I_2(x, r(x)), f s I_2(x, r(x)))
f(x) = sgn(sub(ssssso(x)), x)
G(m, n) = r((m - 2) + (n - 3), 5) //для неё (условие)
G(m, n) = r sum (A I_1(m ,n), B I_2(m ,n))
A(x) = sub(I_1(x), sso(x))
B(x) = sub(I_1(x), ssso(x))